DETERMINATION OF THE EFFECTIVENESS OF THE REGULATORY LEGAL ACT AND ENFORCEMENT IN THE LEGAL MONITORING (METHODOLOGICAL AND APPLIED ASPECTS) - Zarab Gazizovich Казиев; Saikou Bakytovich Айсин (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The article It outlines the main methodological and applied aspects of evaluating the effectiveness of legislation and practice in the process of legal monitoring.